1986
DOI: 10.1073/pnas.83.5.1213
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms produce a collagen-like substance detected by the garter snake vomeronasal system.

Abstract: Earthworms (Lumbricus terrestris) produce a chemical substance that is readily detected by and serves as an attractant for garter snakes (Thamnophis sirtalis). This chemoattractant is sensed by the vomeronasal system ofsnakes. Amino acid analysis of the chemoattractant revealed a high hydroxyproline/proline ratio and large amounts of serine and threonine. More than one-third of the residues were glycine. No hydroxylysine and no cysteine were present. Carbohydrate analyses revealed a high content of galactose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The segregation of the rodent olfactory system into two compartments, the VNO housing the microvillous receptor cells and the main OE housing the ciliated ORNs, led to the belief that ciliated ORNs mediate detection of general odorant cues, whereas microvillous ORNs are responsible for pheromone detection. This view is overly simplistic when applied to vertebrates in general; e.g., the VNO of snakes, which contains microvillous ORNs, is capable of detecting feeding cues (Burghardt, 1970; Kirschenbaum et al, 1986), and the main OE in rodents also responds to sex pheromones (Sipos et al, 1995; Navarro Becerra et al, 1996). For fish, in which the three types of ORNs are intermingled in a single OE, the results of various studies have been contradictory even for a single species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The segregation of the rodent olfactory system into two compartments, the VNO housing the microvillous receptor cells and the main OE housing the ciliated ORNs, led to the belief that ciliated ORNs mediate detection of general odorant cues, whereas microvillous ORNs are responsible for pheromone detection. This view is overly simplistic when applied to vertebrates in general; e.g., the VNO of snakes, which contains microvillous ORNs, is capable of detecting feeding cues (Burghardt, 1970; Kirschenbaum et al, 1986), and the main OE in rodents also responds to sex pheromones (Sipos et al, 1995; Navarro Becerra et al, 1996). For fish, in which the three types of ORNs are intermingled in a single OE, the results of various studies have been contradictory even for a single species.…”
Section: Discussionmentioning
confidence: 99%
“…Although many nonvolatile odorants are socially relevant signals in rodents, the commonly stated hypothesis that the VNO detects only pheromones is oversimplified and not generally applicable across all species (Johnston, 2000). For example, the VNO of snakes detects feeding‐related cues (Burghardt, 1970; Kirschenbaum et al, 1986; Halpern et al, 1997).…”
mentioning
confidence: 99%
“…The vomeronasal organ can also mediate the detection of and the innate response to chemical signals of individuals of species different from that of the receiver, the so‐called allomones. Among others, these include prey chemicals detected by their predators, as for the vomeronasal detection of an earthworm glycoprotein by snakes (Kirschenbaum et al, ). Conversely, some preys innately react with defensive (antipredatory) behaviors to the detection of predator allomones.…”
Section: Old Theories On the Roles Of The Olfactory And Vomeronasal Smentioning
confidence: 99%
“…Comparative studies of two earthworms, Neris (a polychaete) and Lumbricus (an oligochaete) showed that Lumbricus earthworm did not contain the acidic disaccharides but had more galactose units [1, 2]. Interestingly, Lumbricus terrestris earthworm produces a collagen-like substance detected by the garter snake [3]. The carbohydrate content of this collagen-like substance, reveals a high content of galactose (11 wt%) with lesser amounts of fucose, mannose, glucose, N -acetylglucosamine (GlcNAc), and N -acetylgalactosamine (GalNAc) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Lumbricus terrestris earthworm produces a collagen-like substance detected by the garter snake [3]. The carbohydrate content of this collagen-like substance, reveals a high content of galactose (11 wt%) with lesser amounts of fucose, mannose, glucose, N -acetylglucosamine (GlcNAc), and N -acetylgalactosamine (GalNAc) [3]. Glycosaminoglycans (GAGs) are composed of repeating uronic acid (glucuronic acid (GlcA) or iduronic acid (IdoA)) residues and either GlcNAc or GalNAc residues.…”
Section: Introductionmentioning
confidence: 99%